Construction of Immune-Chromatographic Indicator Elements for Burnet Rickettsia Detection - L. A. Basharova; S. P. Yarkov; S. I. Tret’Yakov; V. N. Zlobin (Проблемы особо опасных инфекций, 2013)
mc/ml, and the elapsed time – 20 minutes. The IE is specific to other members of the family Ricketsiaceae, for instance to R. prowazekii , to antigen complexes of R. prowazekii and R. sibirika , as well as to vaccinia virus (L-IVP strain). The IE engineered can be used for rapid indication of Burnet Rickettsia at different stages of laboratory investigation. Span time reduction, lack of necessity to perform any accessory technological operations, visual and (or) automatic registration of the results build up premises to observe immune-chromatographic method for Burnet Rickettsia detection as one of the alternatives for identification of these microorganisms under field conditions when monitoring ambient environment objects.